Problems of forming informative competence of future teachers of physical culture in the context of informatization of education. - Karlo V.G (Kharkov National Pedagogical University, 2012)
In theory, forming of informative competence for the future teachers of physical education in the process of education is grounded. It is exposed, that forming of informative competence of future teacher of physical culture is one of major constituents of alteration of the system of physical education. It is shown that for the successful decision of problems of forming of informative competence of future teacher of physical culture expediently complex to conduct research on forming of computer literacy, informative culture in the field of knowledge "Physical education, sport and health of a man". It is well-proven that introduction of front-rank technologies in the process of preparation of future teachers will allow to prepare the socially developed personality, competent teacher, specialist of the industry. Forming for the students of informative competence will help them to understand the economic, legal and social aspects of the use of information, observe ethics and legal norms during realization of access and use of information.